The comic in Lecoq’s pedagogy: exercise with larval masks (Móin-Móin Magazine - Studies in the Art of Puppetry, 2022)
The article proposes to analyze ways in which Jacques Lecoq's (1921-1999) pedagogy works with the comic. To do so, we took an improvisation exercise with larval masks carried out at his school, from which we established relationships with some characteristics of comedy according to Henri Bergson (1859-1941). I emphasize technical aspects learned in the first year of Lecoq's school, when principles of play and theatrical creation based on the body and improvisation are developed, tracing possible connections of these practices with the production of the comic.
Keywords: Jacques Lecoq; theatre pedagogy; comic; larval mask; acting